Design of a single power supply for a gate drive circuit and a control circuit for a three phase inverter (Thai) - Manerutanaporn, Jaruwat; Daosawang, Mongkol; Buasri, Panhathai; Choeisai, Krit (Asia-Pacific Journal of Science and Technology, 2017)
This paper proposes the design of a single power supply for a gate drive circuit and a control circuit for a three phase inverter for an industrial plant. The proposed design uses diodes to allow the current flow to protect from short circuit current in the circuit and capacitors to supply stable power to the gate drive circuit. Furthermore opto-isolators are used in the design to isolate the control circuit and the high power side that contains MOSFETs switching at a high frequency. A single power supply is used to drive the gates.The experimental results show that the proposed method is fully functional when connected to a three-phase induction motor. The smaller physical size of the inverter results in system cost reduction compared with an inverter used in the conventional method.